Hart's war - Katzenbach, John (Ballantine Books, 2002)
In a prison camp for American airmen in World War II Germany, a black pilot goes on trial for the murder of a racist Southern officer. Flight navigator Tom Hart, a former Harvard law student, volunteers as a defense lawyer and discovers a conspiracy. The trial is supervised by the Gestapo